Organically based strategies used by small-scale farmers in Lesotho for the sustainable management of soilborne diseases - Kena, Mapotso Anna (University of the Free State, 2002)
Damping-off of vegetable seedlings caused by Rhizoctonia solani Kuhn., Pythium ultimum Trow. and Fusarium oxysporum Schlecht. cause serious losses in seedbeds in Lesotho. Composts prepared from poultry, cattle, pig and sheep manure and commonly used by Lesotho farmers were shown to decrease disease severity and increase plant biomass. Cattle, pig and poultry manure composts gave the best disease suppression and stimulated the growth of vegetable seedlings. Composted sheep manure however, did not suppress damping-off nor increase seedling biomass. Seed germination was also significantly suppressed in this compost. High concentrations of phytotoxic elements were possibly responsible for this phenomenon. Disease suppression was also investigated in field studies. Composted cattle, pig and poultry manures significantly suppressed seedling damping-off. Sheep manure compost was also able to reduce damping-off severity under field conditions but to a lesser extent than the other three composts. General microbial activity in field soil including fungal populations present in the four tested composts was evaluated in the laboratory using FOA. Composted cattle, pig and poultry manure displayed a significantly higher level of microbial activity and consequently yielded more fungal colonies. The lowest microbial activity was observed in composted sheep manure. Research conducted on the suppression of R. so/ani, P. ultimum and F. oxysporum with crude extracts of Rhamnus prinoides L. Herit, Artemisia afra Jacg. ex Willd., Leucosidea sericea Eckl. & Zeyh and Melia azedarach L, confirmed their ability to suppress these pathogens. Mycelial growth of R. so/ani, F. oxysporum and P. ultimum was inhibited in vitro by extracts of R. prinoides, L. sericea and A. afra. The growth of these pathogens was however not significantly suppressed by extract of M. azedarach. The plant extracts were also able to suppress damping-off of seedlings when added to soil. Populations of R. solani, F. oxysporum and P. ultimum in soils treated with these extracts were also significantly reduced. Disease reduction was highest 7 and 14 days after treatment with the extracts. The combination of composted animal manures with plant extracts resulted in a reduction of general soil microbial activity, especially fungi. Microbial activity was most reduced in cattle, pig and poultry manure composts while the microbial activity in composted sheep manure was not affected by plant extracts. In fact in some cases, the application of plant extracts resulted in an increased microbial activity in sheep manure. Disease suppression in greenhouse studies was not negatively or positively affected by the addition of plant extracts. The present study confirms that composted manure of cattle, poultry and pig as used by Lesotho farmers, can be effectively used to control damping-off of vegetable seedlings in seedbeds. The use of sheep manure is however still questionable due to its negative effect on seed germination and general plant growth. Extracts of L. sericea, A. afra, R. prinoides and M. azedarach as used by Lesotho farmers, also have the potential to suppress soilborne pathogens. They can be used to control soilborne diseases either individually or in combination with animal manure composts.

Vooropkoms-afsterwing van groentesaailinge wat deur Rhizoctonia so/ani Kuhn., Pythium ultimum Trow. en Fusarium oxysporum Schlect. veroorsaak word, lei soms tot ernstige verliese in saadbeddings in Lesotho. Kompos wat met bees-, vark-, skaap- en hoenderbemesting voorberei is, en algameen deur selfversorgende boere in Lesotho benut word, is in die glashuis- en veldproewe met betrekking tot hul siekteonderdrukkende vermoeëns ondersoek. Met die uitsondering van skaapbemesting, was die intensiteit van saailingsiektes wat deur bogenoemde patogene veroorsaak word beduidend minder terwyl die biomassa van saailinge ook aansienlik toegeneem het. Kompos wat met skaapbemesting voorberei is het ook saadontkieming onderdruk, In verskynsel waarvoor hoë konsentrasies fitotoksiese verbindings moontlik verantwoordelik was. Die algemene mikrobiese aktiwiteit van gewone leemgrond asook die van die vier tipes kompos hierbo genoem, was in die laboratorium met behulp van fluorosien-diasetaat (FOA) geëvalueer. Kompos wat met bees-, vark-, en hoenderbemesting voorberei is. het 'n beduidende hoër vlak van mikrobiese aktiwiteit getoon en dienooreenkomstiog ook meer swamkolonies in kultuur opgelewer. Skaapbemesting het In beduidend laër mikrobiese aktiwiteit as grond en die ander bemestingstowwe getoon. Navorsing is op die siekte-onderukkende vermoë van ru-plantekstrakte van Rhamnus prinoides L. Herit, Leucosidea sericea Eck!. & Zeyh., Artemisia afra Jack. ex Willd en Me/ia azedarach L. uitgevoer. AI vier plantsoorte het vooropkomsafsterwing van groentesaailinge, wat deur bogenoemde patogene veroorsaak word, aansienlik verminder wanneer dit tot grond-groeimedia toegvoeg was. Miseliumgroei van die drie patogene was ook in vitro deur ekstrakte van R. prinoides, L. sericea, en A. afra geïnhibeer maar nie deur dié van M. azedarach nie. Siekte-onderdrukking was mees beduidend tussen sewe en veertien dae na behandeling van die grond met die onderskeie ekstrakte. In Kombinasie van gekomposteerde dierebemestingstowwe met plantekstrakte het tot 'n afname in die algehele mikrobiese aktiwiteit daarvan gelei. Die grootste afname het in bees-, vark-, en hoenderbemesting plaasgevind terwyl kompos met skaapbemesting nie beïnvloed was nie. In sommige gevalle het daar met skaapbemesting selfs 'n toename in mikrobiese aktiwiteit plaasgevind. Die siekte-onderdrukkingsvermoë van die groeimedia het stabiel gebly. Die studie bevestig dat die gekomposteerde dierebemestings wat selfversorgende boere in Lesotho gebruik effektief is in die bekamping van saailingsiektes van groentegewasse. Voorts, het ru-plantekstrakte van R. prinoides, L. sericea, M. azedarach en A. afra ook potensiaal, alleen of in kombinasie met dierebemestingstowwe, om grondgedraagde plantpatogene te onderdruk.
Thesis (Ph.D. (Plant Sciences (Plant Pathology))--University of the Free State, 2003
Keywords: Soilborne plant diseases -- Lesotho; Soil amendments -- Lesotho; Phytopathogenic microorganisms -- Control -- Lesotho